Stibnite Nanoparticles as a New Stabilizer for Poly (Methyl Methacrylate) Exposed to Gamma Irradiation - Albuquerque,Marília Cordeiro Carneiro de (2015)
AbstractPoly (methyl methacrylate), PMMA, may be used in manufacturing of devices, which are exposed to gamma irradiation. However, the polymer undergoes significant changes in its properties during process and the use of additives is a common form to stabilize the PMMA matrix. In this way, stibnite was synthesized by sonochemical method and the amorphous powder constituted of nanospheres was obtained and investigated as additive. Commercial PMMA containing stibnite nanoparticles (ST-NP) was investigated and the samples were irradiated with gamma radiation (60Co). Our results showed that the addition of ST-NP at 0.3 wt% into the PMMA decreased the number of main chain scissions caused by the irradiation process, resulting in radiolytic stabilization of the polymer matrix. Analyses of mechanical properties showed influence of the ST-NP in the physical behavior of PMMA. Our findings suggest that stibnite nanoparticles are an effective additive for PMMA used in application of radiation resistance.